Anthropometric characterization of child and teenagers and nutritional relationship in the field of Monte Sinaí. Guayaquil - Ecuador - Gordillo A., Mercedes M.; Sánchez Gordillo, Olinda (Revista Universidad de Guayaquil, 2017)
This study determines the anthropometric characterization in relation to the nutritional status of the child population - Youth. The project was carried out in the Sector of Sinai´s Mount. Guayaquil - Guayas, Ecuador; in the period from May 2014 to September 2016, based on focus groups Subcentro Health, CNH, CIBV the MIES and Educational Units of Sinai´s Mount. Through training habits and eating habits were advised - nutritional correct, a sample of 787 children and adolescents (neonates, young infants and elderly, preschool, children and adolescents) was determined by taking anthropometric measurements: weight, height and perimeter cephalic in children up to 12 years and BMI in adolescents aged 13-19 years. This investigation revealed that according to the age indicator / weight / height / head circumference and Body Máss Index 333 (42.31%) of the infanto - youth sector, presented some degree of malnutrition, 358 (45.49%) normal weight and 96 (12.19%) overweight and obesity. It becomes visible that the child population - youth accused a high prevalence of mild chronic malnutrition in relation to severe chronic malnutrition, which shows an improvement in the nutritional status of the sector. In addition it was found that overweight and obesity increased compared with previous studies.
Keywords: eutrophic; malnutrition; obesity; overweight